2001
DOI: 10.1046/j.1526-0976.2001.51012-8.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cervical and Breast Cancer: Is Obesity an Unrecognized Barrier to Preventive Care?

Abstract: Ann Intern Med 2000;132:697–704 Data from the National Health Interview Survey were used to assess rates of Pap smear screening among normal and overweight/obese women. Overall screening rates, defined as a self‐report of any Pap within 3 years, were 83% for normal‐weight women; 77% to 80% for obese women, depending upon age and race. These rates were significantly lower for overweight/obese women compared to normal‐weight women. Obesity was linked to age, race, a lack of private health insurance, lower socioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
190
3
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(201 citation statements)
references
References 0 publications
2
190
3
6
Order By: Relevance
“…Based upon these findings, it is perhaps not surprising that many overweight adults report that physicians do not understand the extent to which overweight causes difficulty in their lives [12]. It has also been suggested that poor patientprovider dynamics might contribute to the lower rates of compliance with preventive and follow-up health care in overweight adults [13][14][15].…”
Section: Methods-thementioning
confidence: 99%
See 1 more Smart Citation
“…Based upon these findings, it is perhaps not surprising that many overweight adults report that physicians do not understand the extent to which overweight causes difficulty in their lives [12]. It has also been suggested that poor patientprovider dynamics might contribute to the lower rates of compliance with preventive and follow-up health care in overweight adults [13][14][15].…”
Section: Methods-thementioning
confidence: 99%
“…Based upon these findings, it is perhaps not surprising that many overweight adults report that physicians do not understand the extent to which overweight causes difficulty in their lives [12]. It has also been suggested that poor patientprovider dynamics might contribute to the lower rates of compliance with preventive and follow-up health care in overweight adults [13][14][15].To our knowledge, no previous study has examined the relationship of weight to satisfaction with care or perceptions of health care providers in adolescents. The characteristics adolescents typically desire in their providers have been found to be different from those of adults [16][17][18][19].…”
mentioning
confidence: 99%
“…Little attention has focused on the mechanics of pelvic examination technique, yet the examination is an intrusive experience for many women who feel exposed and lack control. 1 Emotional distress and fear of pain are cited as reasons for reduced adherence to cervical screening especially among adolescents, 2 racial/ethnic [3][4][5] and sexual minority groups, 6 obese women, 7 victims of sexual assault and other trauma, 8 and women with disabilities. 9 Therefore, examination should be limited to components with proven utility and should be performed with cultural sensitivity and procedural excellence, especially in clinical situations that require particular finesse.…”
mentioning
confidence: 99%
“…El estigma de obesidad genera comportamientos que no contribuyen al control del peso 29 , tales como el retraso o evitación en la búsqueda de prestaciones médicas 30,31 , menor motivación por realizar actividad física 32,33 o una ingesta calórica superior a la recomendada por los especialistas 19,34,35 . Además, la discriminación derivada del estigma, se ha asociado a presión arterial elevada, lo que pone en un doble riesgo a los obesos 28,36,37 .…”
Section: Consecuencias Del Estigma De Obesidad En Las Víctimasunclassified